The Role Of Counselors In Creating Family Harmony Due To Lack Of Communication - Muhammad Reza Mahendra (Tunas Institute, 2024)
In every individual wantss fanily harmony in forming a family. In realizing a harmonious household, there are often problomatic phoenomena in the family such as quarrels. Jralousy , infidelity, income differences in life principles and even ending the marriage or divorce.This research is using libraly research method witch aims to find out effort to create a harmonious family due to lack of find out effort to create a harmonious family to lack of communication by using abehavior approach. With behavioral approach, the counselor caan help clients not to demand and feel annoyed trough chaous, conselees in RBTcan exprees some negative felling, but the main goal is to help counselees so as not to give emotional responses beyond what is approriate to an event.